Preclinical safety evaluation of the ethanolic extract from the aerial parts of Gomphrena celosioides Mart. in rodents - Macorini, Luis Fernando Benitez; Maris, Rafael Souza; Teixeira, Thiago Chaves; Ito, Caren Naomi Aguero; Kuraoka-Oliveira, Angela Midori; Bacha, Flávia Barbieri; Mejia, Angela Julieth Buitrago; Salvador, Marcos José; Kassuya, Cândida Aparecida Leite; Arena, Arielle Cristina [UNESP] (Elsevier, 2022)
The toxicological potential of the ethanolic extract from Gomphrena celosioides (EEGC), a medicinal plant used as a natural analgesic, was investigated in acute and subacute toxicity models in rodents. For the acute toxicity test, 2000 mg/kg of EEGC was administered orally to male and female Wistar rats, while Swiss mice received 75, 150 or 300 mg/kg of EEGC for the subacute toxicity test. Animals treated with an only dose of 2000 mg/kg EEGC showed no clinical signs of toxicity, indicating that the LD50 is higher than this dose. The repeated treatment with EEGC did not cause adverse clinical signs, or lesions in target tissues. According to the Globally Harmonized System of classification, the EEGC dosages can be in Category 5 which is the least toxic or non-toxic one.
Keywords: Acute toxicity model; Amaranthaceae; Gomphrena celosioides; Mice; Rats; Safety; Subacute toxicity model